Historical Aspects of the Development of Ecological Activity in the Solution of Ecology Problems of the South Aral Sea (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the study of historical aspects in the development of environmental activities in the South Aral region. In connection with the environmental situation that has developed in recent years, the relevance of the study of solutions to environmental problems is especially relevant in this region. It was noted that in Uzbekistan, including in the South Aral Sea region, in order to strengthen the foundations of sustainable development, a set of measures is being taken to improve the socio-ecological situation in the country.